Komunikasi Profetik Perspektif Islam Terhadap Ujaran Kebencian di Media Sosial - Reiza Praselanova (Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2022)
Hate speech causes great harm. Its spread is difficult to control on social media. Social media has the power to change people's behavior. The flow of information and social media users continues to grow. Islamic perspective through prophetic communication as a prophetic social science theory against hate speech. Prophetic communication based on Kuntowijoyo's paradigm has three values, namely, humanism, liberation and transcendence. Qualitative Research Literature Review allows studying data sources from hadiths. The focus of the research is on the pattern of prophetic communication in response to hate speech. Integrated professional communication per device. The value emphasizes goodness in words and interactions, the value of freedom that does not go too far to prevent crime and the value of awareness of the relationship between human faith and God in social life, including on social media.